Vergleich der Sehschärfenbestimmung mit Landolt-Ringen versus Zahlen = Comparison of visual acuity measurement with Landolt rings versus numbers - Rohrschneider, Klaus; Spittler, Axel Raymond; Bach, Michael (Der Ophthalmologe, 2019)
PurposeLandolt rings are commonly used for the measurement of visual acuity, especially for legal purposes. For multiple reasons, in clinical practice these optotypes are not in use and not practical. Therefore, the difference between visual acuity tested with Landolt rings as opposed to numbers was evaluated.MethodsVisual acuity measurements of 2335 eyes from 1394 patients (aged 5-98 years, median 51 years) were retrospectively analyzed at the Low Vision Department of the University of Heidelberg. The patients had a broad range of ophthalmological disorders. In all patients the measurement of visual acuity was performed with numbers as well as Landolt rings according to DIN 58220. Visual acuity was determined in LogMAR and compared between the two optotypes.ResultsCorrelation between both optotypes was high with r2 = 0.927 but there was a pronounced mean difference in visual acuity of 0.13 ± 0.14 LogMAR. Using numbers, visual acuity was 0.13 LogMAR higher, somewhat more than one line. These differences were mostly independent of visual acuity and increased slightly with age; however, the variations were greater for lower visual acuity.ConclusionWhereas in clinical practice visual acuity is typically determined using numbers and early treatment diabetic retinopathy study (ETDRS) charts are the gold standard for a scientific assessment of visual acuity, only the use of Landolt rings enables an examination without the influence of form recognition. The use of Landolt rings is therefore valid for legal reasons in Europe according to EN ISO 8596 and in Germany according to DIN 58220. Comparing Landolt rings with the Snellen E chart or LEA symbols, these results confirm previous reports that visual acuity measured with Landolt rings results in lower visual acuity. On average visual acuity is approximately one line worse than when tested with numbers, a fact that has to be taken into account when comparing different examination results. This may be explained by incorrect correlation of the used numbers exceeding the allowed difference in eligibility of 0.05 LogMAR. Hence, it is important for legal assessment to measure visual acuity correctly with Landolt rings.
Gesehen am 26.11.2019